2019
DOI: 10.3389/fpsyg.2019.00228
|View full text |Cite
|
Sign up to set email alerts
|

Memory of Ensemble Representation Was Independent of Attention

Abstract: The hierarchical view of working memory suggested that object ensemble could also be stored into working memory by treating ensemble properties as single “unit.” However, it remains unclear whether ensemble representation in working memory is vulnerable to attention demanding. The present study designed a dual-task paradigm constituting of a memory retaining task and an attention-demanding arrow flanker task. Participants were firstly presented an array (4 or 9) of facial images with neutral expressions and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Based on these previous findings, it seems that the ensemble coding of facial identity information could be unique. However, Leib et al (2014) found that the precision of mean identity representations improved as the set size increased, which is inconsistent with the findings reported by Neumann et al (2017) and Peng et al (2019) . We propose that the different results might be due to stimulus variance in a set.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Based on these previous findings, it seems that the ensemble coding of facial identity information could be unique. However, Leib et al (2014) found that the precision of mean identity representations improved as the set size increased, which is inconsistent with the findings reported by Neumann et al (2017) and Peng et al (2019) . We propose that the different results might be due to stimulus variance in a set.…”
Section: Discussionmentioning
confidence: 89%
“…We propose that the different results might be due to stimulus variance in a set. Neumann et al (2017) and Peng et al (2019) used more than 40 faces with different identities as the experimental material, while Leib et al (2014) employed morphing stimuli created from three faces, and the present study used morphing stimuli created from two faces. Therefore, the number of faces used in the different studies may have caused different stimulus variances in a set.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is the case even if explicit ensemble representations do not demand (explicit or implicit) representation of individual features (Ward et al, 2016). The numerous observations of ensemble representations formed in the absence of attention (e.g., Corbett & Oriet, 2011;Peng et al, 2019;Whitney & Yamanashi Leib, 2018) provide empirical support to this suggestion.…”
Section: Measures Of Awarenessmentioning
confidence: 91%